Dietary supplements in fitness centers: body management and health risks - Alan Camargo Silva; Maria Isabel Brandão de Souza Mendes; Sílvia Maria Agatti Lüdorf (Revista da Educação Física)
The purpose of this study was to explore the meanings of supplement use among those who engage in physical activity in fitness centers. A qualitative study was carried out based on 67 questionnaires answered on the internet by practitioners of physical training. There was also an observation of the groups in the Facebook, the dynamic and other aspects such as discussions, messages, profiles and images. It was detected that physical activity practitioners care more about the quantity of substances ingested than any other factor that may lead them to suffer certain health risks. They believe that so-called "excesses" may cause diseases to the internal organs. Although the participants believe that their own consumption of supplements does not compromise their health, a biomedical authority is crucial for them to recognize whether or not they are at risk. The consumption of supplements can vary depending on what is understood to be excessive and which risks may compromise the body. There are many motivations for managing these substances. Health risks should not be analyzed solely from a biomedical perspective, but also addressed by the socio-cultural logic of the perceptions and meanings attributed by the subjects to the body and the management thereof.